A challenging case of keratoconjunctivitis medicamentosa with necrotizing scleritis - Shakeel, Tarannum; Das Gupta, Sushobhan (Indian Journal of Case Reports, 2024)
We report a case of keratoconjunctivitis medicamentosa in a 64-year-old female. She was operated for cataract 4 months back and treated for viral keratitis at present. Ocular examination revealed inferior sterile corneal melt with ischemic necrotizing scleritis and ischemic necrosis of tarsal and lower fornix conjunctiva. Keratoconjunctivitis medicamentosa was diagnosed. Tenonplasty with multilayered amniotic membrane grafting and mucous membrane grating of the tarsal plate was done to which she responded well. Chemical irritation of the ocular surface by topical drops may result in keratoconjunctivitis medicamentosa. A high index of suspicion is required for the accurate diagnosis of such a visually debilitating condition.